2012
DOI: 10.1001/jama.2012.253
|View full text |Cite
|
Sign up to set email alerts
|

Does This Patient Have a Severe Upper Gastrointestinal Bleed?

Abstract: A 62-year-old man presents to the emergency department after an episode of syncope following several weeks of fatigue. He has a history of upper gastrointestinal bleeding (UGIB) due to peptic ulcer disease. His blood pressure is 90/60 mm Hg, pulse of 105/min, and a black, foul-smelling stool is found upon rectal examination. Blood test results show a hemoglobin level of 6.5 g/dL, a creatinine level of 1.0 mg/dL, and a serum urea nitrogen level of 55 mg/dL. Would the results of a nasogastric lavage help determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(109 citation statements)
references
References 52 publications
2
99
0
8
Order By: Relevance
“…The study subjects consisted of consecutive cases, and the need for an EI was evaluated based on high-risk stigmata of recorded endoscopic images that were reviewed retrospectively in this relatively large-scale study. The present study revealed that the BUN-Cr ratio and GBS were also independent risk factors in predicting the need for EI; these results are consistent with those of a previous study [8]. Therefore, our study results seem to be reliable.…”
Section: Discussionsupporting
confidence: 93%
“…The study subjects consisted of consecutive cases, and the need for an EI was evaluated based on high-risk stigmata of recorded endoscopic images that were reviewed retrospectively in this relatively large-scale study. The present study revealed that the BUN-Cr ratio and GBS were also independent risk factors in predicting the need for EI; these results are consistent with those of a previous study [8]. Therefore, our study results seem to be reliable.…”
Section: Discussionsupporting
confidence: 93%
“…Initial patient assessment and hemodynamic resuscitation should be performed simultaneously (strong recommendation, very low-quality evidence). 8, 10 …”
Section: Initial Assessmentmentioning
confidence: 99%
“…In another randomized controlled study, 4 of 112 patients (3.6%) with severe hematochezia had upper GI bleeding [35]. According to a meta-analysis, clinical findings indicating upper GI bleeding are black stool, bloody or coffee grounds aspirate from the nasogastric tube, and BUN:Cr ≥30 [37]. Therefore, in patients with severe dark or bright red stool, upper GI bleeding needs to be ruled out by calculating BUN:Cr and inserting a nasogastric tube or performing upper GI endoscopy.…”
Section: Explanationmentioning
confidence: 99%